Analisis Pemenuhan Kebutuhan Ruang Terbuka Hijau Kota Medan - Siregar, Rahmadhani Ulfah; Sabrina, T.; Lubis, Satia Negara (Jurnal Ilmiah Global Education, 2024)
This research aims to analyze the area and percentage of green open space in Medan city, formulate the direction of recommendations and strategies to meet the needs of public green open space. This research is descriptive in nature using quantitative methods. The primary data of the research was obtained from 40 respondents consisting of the Medan City Environment Office, the Housing and Settlement Office of Cipta Karya and Spatial Planning and the Community. The results showed that green open space in Medan City has an area of 11642.90 Ha or 41.35% of the overall total in Medan City and there are 14 sub-districts that do not meet the established green open space requirements. The implication of this research contributes to the importance of urban planning practices. Strategies to increase the provision of green open space in Medan City can be achieved by applying a combination of intensification and extensification measures in the development of green open space.